Special Problems of the Deaf Under the Education for All Handicapped Children Act of 1975 - Donald W. Large (Washington University Law Quarterly, 1980)
With the benefit of these years of hindsight, the purpose of this Article is fourfold: (1) To explore the anticipated problems of the Act's implementation and to show that several problems have been more severe than was predicted by most writers. (2) To analyze the Act's basic assumption regarding placement of handicapped children as nearly as possible in a "normal" situationcommonly known as "mainstreaming"-and to show that, in many situations, that assumption has proven to be more harmful than helpful. (3) To distinguish between types of handicaps, showing how the Act-by not distinguishing between types of handicaps-produces different effects for different groups of children. (4) To explain the unique nature of deafness as a handicapping condition and to discuss the special problems of deaf children under the Act.
Keywords: Deaf education; Disabled children; Mainstreaming (Education); Education for All Handicapped Children Act of 1975; United States